2021
DOI: 10.1155/2021/9979843
|View full text |Cite
|
Sign up to set email alerts
|

Acacetin Protects Myocardial Cells against Hypoxia-Reoxygenation Injury through Activation of Autophagy

Abstract: Ischemic heart disease is a leading cause of mortality and morbidity worldwide. We previously demonstrated that acacetin protects against myocardial ischemia reperfusion injury in rats, although the underlying mechanism remains to be elucidated. In the present study, we investigated the effects of acacetin on autophagy during hypoxia/reoxygenation (H/R) injury by exposing H9c2 myocardial cells to H/R with or without acacetin pretreatment during hypoxia. Our results show that acacetin significantly increased ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Another study found that the improved effects were mediated by activating the PI3K/AKT/mTOR signaling pathway [8]. Furthermore, acacetin protects cardiomyocytes against hypoxia/reoxygenation injury via AMPKmediated Nrf2 activation [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study found that the improved effects were mediated by activating the PI3K/AKT/mTOR signaling pathway [8]. Furthermore, acacetin protects cardiomyocytes against hypoxia/reoxygenation injury via AMPKmediated Nrf2 activation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have demonstrated that acacetin can improve cardiac hypoxia/reoxygenation injury via reducing lipid peroxidation and enhancing antioxidant capacity [13]. Another study found that the improved effects were mediated by activating the PI3K/AKT/mTOR signaling pathway [8]. Furthermore, acacetin protects cardiomyocytes against hypoxia/reoxygenation injury via AMPK-mediated Nrf2 activation [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have confirmed that the antioxidant, anti-inflammatory, and antiapoptotic effects of acacetin on cells are mediated by AMPK-mediated Nrf2 activation [ 35 ]. Interestingly, a recent study demonstrated that autophagy is involved in the process of alleviation of myocardial hypoxia/reoxygenation injury by acacetin; that is, acacetin enhanced autophagy through activating the PI3K/Akt/mTOR pathway [ 36 ].…”
Section: Pharmacological Effects On Cardiovascular Diseasesmentioning
confidence: 99%
“…To identify natural-source-derived pharmacological drugs that could be useful for cancer therapy by targeting STAT3 activation pathways, focus has been placed on acacetin isolated from plants, such as Tunera diffusa, Propolis, Dracocephalum moldavica, Betula pendula, Robinia pseudoacacia, Flos Chrysanthemi Indici, Chrysanthemum, Safflower, Calamintha, and Linaria species [ 16 , 17 ]. As a natural flavonoid compound, acacetin (5,7-dihydroxy-4′-methoxyflavone) has antioxidative and anti-inflammatory effects and has exhibited extensive therapeutic effects on numerous cancers [ 17 , 18 , 19 , 20 , 21 ]. However, the elaborate molecular mechanisms through which ACN brings about these effects and its potential in vitro efficacy on HCC progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%